Training on Statistical Data Analysis Techniques in Classroom Action Research into Scientific Papers for Teachers of SDN Inpres 2 Talise Palu City - Fadjriyani; Hartayuni; Iman Setiawan (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Writing skills are essential for teachers, especially when writing scientific papers related to their fields of expertise. However, many teachers, including those at SDN Inpres 2 Talise, Palu City, find writing scientific papers challenging. They often struggle with writing Classroom Action Research (CAR) reports and analysing the resulting data. These CAR reports are meant to be written into scientific papers, which are crucial for career advancement and functional position promotions. This community service program aims to enhance teachers' writing skills by training them in statistical data analysis techniques. The focus is on using tools such as SPSS to effectively process CAR data and independently write scientific papers. By participating in this program, teachers at SDN Inpres 2 Talise gain a deeper understanding of statistical analysis methods relevant to research writing, including basic statistical concepts, regression analysis, variance analysis , and other data analysis techniques.. The result of this service program is an increase in the ability of teachers at SDN Inpres 2 Talise, Palu City in processing data using statistical tools. Therefore, the quality of scientific papers submitted in several accredited national journals is better.